2011
DOI: 10.1007/s10695-011-9552-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of arachidonic acid on the endocrine and osmoregulatory response of tilapia (Oreochromis mossambicus) acclimated to seawater and subjected to confinement stress

Abstract: In previous studies in freshwater tilapia (Oreochromis mossambicus), dietary supplementation with arachidonic acid (ArA; 20:4n - 6) had considerable, opposing effects on the main ion-transporting enzyme Na(+)/K(+)-ATPase in gills and kidneys and changed the release of osmoregulatory hormones, such as cortisol. The present study was performed to assess the influence of dietary ArA on (1) the osmoregulatory capacity of tilapia acclimated to seawater (SW) (34‰) and (2) the osmoregulatory imbalance associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Results obtained in the present study corroborate the effect of different fatty acids on the release of cortisol in marine fish, previously described both in vivo ( 6 , 8 , 16 – 19 , 51 , 52 ) and in vitro ( 9 , 21 ) . In agreement with the results previously obtained in gilthead sea bream under similar superfusion conditions ( 21 ) , both EPA and ARA induced an increase of cortisol release in ACTH-stimulated inter-renal cells of European sea bass.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results obtained in the present study corroborate the effect of different fatty acids on the release of cortisol in marine fish, previously described both in vivo ( 6 , 8 , 16 – 19 , 51 , 52 ) and in vitro ( 9 , 21 ) . In agreement with the results previously obtained in gilthead sea bream under similar superfusion conditions ( 21 ) , both EPA and ARA induced an increase of cortisol release in ACTH-stimulated inter-renal cells of European sea bass.…”
Section: Discussionsupporting
confidence: 92%
“…As far as we know, there are no studies in fish on the effect of the different ARA metabolites in steroidogenesis, although the implication of COX-derived metabolites in cortisol release has been suggested in fish ( 17 19 , 51 , 68 ) . Ganga et al ( 21 ) demonstrated that the role of ARA and EPA as modulators of the release of cortisol from ACTH-stimulated inter-renal cells is mediated, at least in part, by COX-2-derived metabolites, since the incubation of head kidney in a indomethacin-enriched medium decreased the release of cortisol from gilthead sea bream inter-renal cells incubated in an ARA- or EPA-enriched medium ( 21 ) .…”
Section: Discussionmentioning
confidence: 99%
“…However, acclimation to salinity was also shown to alter composition of PUFAs, e.g. in tilapia, Oreochromis mossambicus, [105], and two mullet species ( Chelon labrosus and Mugil cephalus ) [106], [107], which was suggested to be due to the substantial energetic demands preceding activation of acclimation processes [106]. Thus, it appears that studies addressing the role of lipid metabolism in terms of fish osmoregulation have not reached a consensus as the data are contradictory (rev.…”
Section: Discussionmentioning
confidence: 99%
“…Van Anholt et al [34] found an increase in the AA content in tilapia (Oreochromis mossambicus) acclimated to seawater, suggesting a possible role of AA in the osmoregulation. However, the rise of AA was more evident in tissues involved in osmoregulation as gills and kidney respect to muscle.…”
Section: Fishmentioning
confidence: 99%